How to Teach Listening in Senior High School - Suryanto, Bradhiansyah Tri (Universitas Nurul Jadid, 2019)
Many teachers considered that listening is the most important skill of any other language skills(Aziez & Alwasilah, 1996). Moreover, the discussion of an issue about the use of authentic listening material is just fierce in listening as it is in reading(Harmer, 2001). However, the teacher should have to look for the simplest method of teaching listening to overcome its difficulties; to teach it effectively; and to achieve the goals of teaching listening successfully, such as teaching students to acquire vocabularies, grammatical understanding, and good pronunciation.The Purposes of the study are to overcome the difficulties in teaching listening; to improve teacher’s creativity in teaching listening; and to provide the teacher with some alternative methods of teaching listening.Based on the study it can be concluded that, first, the effective listening will produce successful listening. Second, the reason of using listening in the classroom is to let the students to hear different varieties and accent of English instead of the voices of their teacher which may be full of idiosyncrasies. Third, the listening materials are geared with the students’ needs, levels, and interests. Fourth, there six principles for listening; Encourage students to listen as often and as much as possible, help students prepare to listen, once may not be enough, encourage students to respond to the content of a listening, not just to the language, different listening stages demand different listening tasks, and good teachers exploit listening texts to the full.